The influence of macroeconomics, banking performance, investment and international trade on public welfare with economic growth variables as intervening variables in G-20 countries - Hakim, Abdul; Ratnawati, Tri; Rahmiyati, Nekky (Edelweiss Applied Science and Technology, 2024)
Social welfare can be interpreted as a condition that shows a state of community life that can be seen from the standard of living of the community while what is meant by social welfare is a state of fulfillment of basic needs that can be seen from a decent house, the fulfillment of clothing and food, education, and health, or it can also be said that social welfare is a state in which a person is able to maximize his utility at a certain budget limit level and a condition in which physical and spiritual needs are met. The G-20 was formed because the international community was disappointed with the failure of the Group of Seven (G7) to find solutions to the global economic problems faced at that time . The need to improve banking performance, as well as increase capital with an adequate level of capital because it has a positive effect on Economic Growth but does not significantly have a positive effect on Social Welfare. And foreign direct investment (FDI) needs to be encouraged by G-20 countries to increase FDI so that it can provide new resources and technology, encourage economic growth because it has a positive effect, Investment does not significantly have a positive effect on improving social welfare. The international trade variable, measured by goods exports (X₄) and economic growth, measured by GDP growth (Y1) have a significant influence on GDP per capita growth (Y2) as an indicator of Public Welfare in G20 countries. This shows that increasing exports of goods can drive economic growth and public welfare in G20 countries. Through a deeper understanding of the factors that influence public welfare in G20 countries, more effective economic policies can be designed and implemented.